The role of pre-hospital ambulance care in the management of road traffic injuries in Addis Ababa (Ethiopia) - Mulugeta Bonsa Ragasa; Tesfaye Girma Legesse; Birhanu Asrat Wudineh; Helina Abayneh (Emergency Care Journal, 2022)
It is estimated that 1.35 million people die each year as a result of road traffic injuries worldwide, with Africa having the highest annual rate. Ethiopia has the highest fatality rate in road traffic accidents, at 79%. There is no well-established emergency medical system in Ethiopia to provide pre-hospital trauma care. A crosssectional study was conducted at selected public hospitals in Addis Ababa. Purposive sampling was used to select the victims who arrived at the emergency department by ambulance. Data was gathered through structured questionnaires administered by an interviewer and a review of victims’ medical records. SPSS Version 25 was used to analyze the data. In this study, 262 victims took part, with a 94% response rate. Patient positioning (50.8%) was the most commonly provided service, followed by bleeding control (43.5%). Within the first 24 hours, 8.4% of the victims died. The first 24-hours of injury-related death were significantly associated with head/neck/spine injury and total pre-hospital time. Action should be taken to increase the availability of necessary equipment in ambulances and the number of paramedic personnel.